A Bioisosteric and Scaffold Hopping Approach for the Design and Synthesis of Double Ring Replacement Analogues of 4‐Aryl‐4H‐Chromenes and in silico Tubulin Inhibitor Studies. Issue 28 (30th July 2018) - Kottha, Thirumalaswamy; Gnanasambandam, Vasuki
Abstract: An eco‐friendly reaction protocol was developed for the synthesis of heterocyclic hybrid scaffolds through bioisosteric replacement and scaffold hopping approach. The isosteric analogues of salicylaldehyde were designed, identified/synthesized and employed in a three component reaction to afford bioisosteric analogues of 4‐aryl‐4 H ‐chromenes. Thus central core swapping of benzene‐pyridine/pyrazole ring on 4‐aryl‐4 H ‐chromenes was achieved under simple one‐pot reaction conditions and easy work‐up. Docking studies show that almost all the compounds possess good binding affinities at the colchicine binding site of tubulin. Abstract : An eco‐friendly reaction protocol was developed for the synthesis of heterocyclic hybrid scaffolds through bioisosteric replacement and scaffold hopping approach. The isosteric analogues of salicylaldehyde were designed, identified/synthesized and employed in a three component reaction to afford bioisosteric analogues of 4‐aryl‐4 H ‐chromenes. Thus central core swapping of benzene‐pyridine/pyrazole ring on 4‐aryl‐4 H ‐chromenes was achieved under simple one‐pot reaction conditions and easy work‐up. Docking studies showed that almost all the compounds possess good binding affinities at the colchicine binding site of tubulin.